Determinación de concentraciones inhibitorias mínimas a algunos antibióticos de las bacterias aisladas de glándula mamaria bovina en San Pedro de los Milagros, Antioquia (2001)
ABSTRACT: An evaluation of 37 strains of microorganisms from the bovine mammary gland was conducted in 1999 in order to measure the antibiotic suceptibility. Of the total bacteria 64,9 % was Streptococcus agalactiae, 18,9 % was Staphylococcus aureus and 16,2 % was coagulase negative Staphylococi. The suceptibility of the bacteria was determined using the Minimum Inhibitory Concentrations method. The antibiotics used were: Ampicillin, Cefazolin, Ciprofloxacin, Clindamicin, Erythromycin, Ofloxacin, Penicillin G, Tetracyclin, Trimethoprim/Sulfa, and Vancomycin. The lactamase test was also conducted. The commercial method utilized was the Vitek biomerieuxâ. The data obtained is presented in a descriptive form. One hundred percent of the Streptococcus agalactiae strains evaluated showed antibiotic susceptibility to the b lactamic group (Ampicillin, Cefazolin, Penicillin G). These bacteria had resistance to the tetracyclin antibiotic in a 87 % of the strains isolated. One hundred percent of the Staphylococcus aureus isolated bacteria showed susceptibility to the penicillin b lactamase resistant and b lactamase protected group, (cefazolin, oxacillin and sulbactam/ampicillin respectively). A 28,6 % of the Staphylococcus aureus showed susceptibility to the b lactamase susceptible penicillin like ampicillin, and penicillin G. 71,4 % of this group was resistant. A 71,4 % of these bacteria was b lactamase producer. One hundred percent of the coagulase negative Staphylococci had susceptibility to penicillin b lactamase resistant and b lactamase protected group (cefazolin, oxacillin, and sulbactam/ ampicillin respectively). A 33,3 % of these bacteria had susceptibility for the b lactamase susceptible group (ampicillin and penicillin G), and a 66,7 % was resistant to this group of antibiotics. A 66,7 % of this bacteria was b lactamase producer. An evaluation of antibiotic susceptibility to the bacteria by using the minimum inhibitory concentration method is more reliable than the diffusion method, consequently, the minimum inhibitory concentrations method should be used in our region in veterinary medicine practice as a routinely procedure.